Submarine groundwater discharge in Dongshan Bay, China: A master regulator of nutrients in spring and potential national significance of small bays - Sun, Yafei; Wang, Guizhi; Weng, Yubin; Li, Qing; Zhang, Fei; Jiang, Weizhen; Dai, Guiyuan; Lin, Wen; Sun, Shengyao; Jiang, Yiyong; Zhang, Yuanjing (Frontiers in Marine Science, 2023)
Despite over 90% of China’s coastal bays have an area less than 500 km2, the geochemical effects of SGD on those ecosystems are ambiguous. Based on mapping and time-series observations of Ra isotopes and nutrients, a case study of small bays (<500 km2), we revealed that submarine groundwater discharge (SGD) predominately regulated the distribution of nutrients and fueled algal growth in Dongshan Bay, China. On the bay-wide scale, the SGD rate was estimated to be 0.048 ± 0.022 m day−1 and contributed over 95% of the nutrients. At the time-series site where the bay-wide highest Ra activities in the bottom water marked an SGD hotspot with an average rate an order of magnitude greater, the maximum chlorophyll concentration co-occurred, suggesting that SGD may support the algal bloom. The ever-most significant positive correlations between 228Ra and nutrients throughout the water column (P< 0.01, R2 > 0.90 except for soluble reactive phosphorus in the surface) suggested the predominance of SGD in controlling nutrient distribution in the bay. Extrapolated to a national scale, the SGD-carried dissolved inorganic nitrogen flux in small bays was twice as much as those in large bays (>2,000 km2). Thus, the SGD-carried nutrients in small bays merit immediate attention in environmental monitoring and management.